The NALCO Water Handbook, Fourth Edition - an Ecolab Company NALCO Water; McGraw-Hill eBooks (New York, N.Y. : McGraw-Hill Education, 2018)
The landmark water use and treatment resource fully updated for optimizing water processes. This industry-standard resource from the world's leading water management company offers practical guidance on the use and treatment of water and wastewater in industrial and institutional facilities.
Cover -- Title Page -- Copyright Page -- Contents -- Foreword -- Preface -- Acknowledgments -- Section 1 Introduction -- 1 The Business Case for Managing Water -- 2 Water Sources and Stressors -- 3 Water Quality -- Section 2 Basic Water Chemistry -- 4 Water Chemistry -- 5 Impurities in Water -- Section 3.1 Applications Impurity Removal -- 6 Raw Water Clarification and Filtration -- 7 Ion Exchange -- 8 Membrane Separation -- Section 3.2 Applications Steam Generation -- 9 Boiler Systems -- 10 Oxygen Removal -- 11 Boiler Feedwater Treatment -- 12 Turbines -- 13 Condensate Systems -- Section 3.3 Applications Cooling Water Systems -- 14 Cooling System Dynamics -- 15 Cooling Water Deposition -- 16 Cooling System Corrosion -- 17 Cooling Water Biology -- 18 Cooling Water Monitoring -- 19 Cooling Water Treatment and Control -- Section 3.4 Applications Water Safety for Building Water Systems -- 20 Legionella and Legionellosis -- 21 Water Management Programs for Engineered Water Systems -- Section 3.5 Applications Post-Treatment -- 22 Primary Effluent Treatment -- 23 Secondary Effluent Treatment -- 24 Tertiary Effluent Treatment -- 25 Heavy Metal Removal -- 26 Sludge Manipulation -- 27 Emulsion Treatment -- 28 Wet Gas Scrubbers -- Section 4 Energy in Water Systems -- 29 Energy Use in Effluent Systems -- 30 Energy in Cooling Systems -- 31 Energy in Steam Systems -- Section 5 Industries -- 32 The Paper Industry -- 33 The Power Industry -- 34 The Oil Field Industry -- 35 The Refining Industry -- 36 The Chemical Industry -- 37 The Aluminum Industry -- 38 The Steel Industry -- 39 The Institutional and Commercial Sectors -- 40 The Food and Beverage Industry -- 41 The Microelectronics Industry -- 42 The Building Materials Industry -- 43 The Automotive Industry -- 44 The Municipal Sector -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- X -- Y -- Z.
Includes bibliographical references and index.
Also available in print edition.
Electronic reproduction.
Mode of access: Internet via World Wide Web.
In English.
Description based on e-Publication PDF.
Keywords: Water -- Handbooks, manuals, etc; Water -- Purification; Sewage -- Purification; Factory and trade waste -- Purification; Water use; Electronic books